I want to simplify the following expression.

$$Y=\text{Bottom} + \frac{\text{Top}-\text{Bottom}}{1+10^{((\log EC50-X))}}$$

$\log$ is base of $10$. Some may know that it's a dose response curve, and I want to solve for $EC50$.

I tried simplifying it but I forgot math long time ago and I couldn't find the answer online.

My problem was the exponential and logarithms part.

Can someone simplify the expression to solve for $EC50$?

Thank you very much.

Edit : And if someone could explain simplifying exponential and logarithm on this one, it would be great as well. I forgot all the math and I would appreciate it.

  • $\begingroup$ To start you off: $10^{\log_{10} x} = x = \log_{10} 10^x$. Also $\log a + \log b = \log(ab)$ and $\log c - \log d = \log(c/d)$ in the same way as $10^{g+h} = 10^g \times 10^h$ and $10^{j-k} = 10^j / 10^k$. $\endgroup$
    – Henry
    Jun 21, 2012 at 21:58
  • $\begingroup$ Does LogEC50-X mean $\log(EC50)-X$ or $\log(EC50-X)$? $\endgroup$
    – Henry
    Jun 21, 2012 at 21:59
  • $\begingroup$ Since its 10^$\log EC50-X$, it wouldn't really make sense if it wasn't $\log(EC50-X)$; otherwise it would simplify immediately. $\endgroup$ Jun 21, 2012 at 22:15

2 Answers 2


Starting with $$Y = \text{Bottom} +\frac{\text{Top}-\text{Bottom}}{1+10^{\log_{10} EC50 -X}}$$

then using $10^{\log_{10} EC50 -X} = EC50 /10^X$ (if that is what you meant) you get $$Y -\text{Bottom} =\frac{\text{Top}-\text{Bottom}}{1+EC50 /10^X}$$ or $$1+EC50 /10^X =\frac{\text{Top}-\text{Bottom}}{Y -\text{Bottom}}$$ i.e $$EC50 =10^X\frac{\text{Top}-Y}{Y -\text{Bottom}}.$$

  • $\begingroup$ Thank you so much. I just didn't remember how minus worked when it is on the exponentials. It was very helpful. Thank you! $\endgroup$
    – js0823
    Jun 22, 2012 at 1:25

Please see the remark at the end, since I don't know for sure what you intend by your formula.

I will use somewhat different notation for ease of typing. Write $w$ for EC$50$, $t$ for top, $b$ for bottom. If I interpret things right, you have $$Y=b+\frac{t-b}{1+10^{\log(w-X)}}.$$

The part you are worried about is the simplest, for in general $10^{\log a}=a$. So your equation can be rewritten as $$Y=b+\frac{t-b}{1+w-X}.$$ the rest is just algebra. First we have $$Y-b=\frac{t-b}{1+w-X}.$$ Flip both parts over. We get $$\frac{1}{Y-b}=\frac{1+w-X}{t-b},$$ and then, multiplying both sides by $t-b$, we get $$\frac{t-b}{Y-b}=1+w-X.$$ Extracting $w$ is now easy. We get $$w=\frac{t-b}{Y-b}-1+X.$$ You may wish to use the simplification $\frac{t-b}{Y-b}-1=\frac{t-Y}{Y-b}$.

About general tips, here is a short list of what you need to know.

  1. $10^{\log a}=a$

  2. $\log(10^b)=b$.

  3. $\log(ab)=\log a+\log b$

  4. $\log 1=0$; $\log(1/a)=-\log a$

  5. $\log(a^c)=c\log a$

  6. $10^{a+b}=(10^a)(10^b)$

  7. $10^{ab}=(10^a)^b$.

If later you ask a specific question or questions you have thought about, someone on this site can show you how to handle the computations.

Remark: If what is intended in the formula is $10^{\log(w)-X}$, this simplifies to $(10^{\log w})(10^{-X})$, and then to $\frac{w}{10^X}$. The rest of the manipulations until close to the end are the same. But ultimately to get $w$ we multiply by $10^X$ instead of adding $X$.

  • $\begingroup$ Thank you so much for your answers. It seems I made everyone confused about the exponentials and logarithms. Your remark is correct. Your general tips were very helpful as well. I wish I could choose more than one correct answers. Thank you! $\endgroup$
    – js0823
    Jun 22, 2012 at 1:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.